THE RELATIONSHIP BETWEEN THE LEVEL OF INDEPENDENCE AND THE QUALITY OF LIFE OF THE ELDERLY AT SABAI NAN ALUIH TRESNA WERDHA SOCIAL HOME IN SICINCIN 2024 - INDRAWANI, YOLA; ASMIATI, ASMIATI; SYAHRUL, SYAHRUL (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
The elderly are a group of people who enter the final phase of life characterised by a decrease in physical, cognitive and social abilities, which can affect their independence and quality of life. This study aims to determine the relationship between the level of independence with the quality of life of the elderly at Sabai Nan Aluih Tresna Werdha Social Home in Sicincin. The method used is quantitative research with descriptive correlation design and crosssectional approach. The sampling technique used quota sampling, obtained 53 samples. Data were collected through a questionnaire that measured the level of independence of the Barthel index and WHOQOL-Bref quality of life. The results showed that 50.9% of the elderly were in the mild dependence category, and 77.4% had poor quality of life. The data were analysed using bivariate analysis with fisher's exact test. The results of the bivariate analysis showed that there was no relationship between the level of independence and the quality of life of the elderly at the sabai nan aluih tresna werdha social home in Sicincin in 2024. with a p-value of 0.217> 0.10. It is hoped that the orphanage will further assist the elderly according to the level of independence in meeting their needs so that the quality of life of the elderly can be maintained properly and further increase the active involvement of the elderly in various activities held by the orphanage so that they still have a more meaningful and meaningful meaning of life.